2018
DOI: 10.1111/jce.13747
|View full text |Cite
|
Sign up to set email alerts
|

Lead I R‐wave amplitude to differentiate idiopathic ventricular arrhythmias with left bundle branch block right inferior axis originating from the left versus right ventricular outflow tract

Abstract: The presence of R-wave amplitude in lead I (≥0.1 mV) is a simple and useful criterion to identify LVOT cusp or endocardium focus in LBRI arrhythmias. A QS pattern in lead I suggests an origin in the anterior RVOT, or less commonly the adjacent LV summit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…Finally, continuous monitoring of the ECG during ablation for a change in QRS morphology should be considered to identify patients who will require further ablation. We have summarized in Table 1 important ECG characteristics indicative VA of specific origins, based on the findings of this study and previous studies in the literature 3,8–15 …”
Section: Location Of Va Qrs Morphology Timingmentioning
confidence: 99%
“…Finally, continuous monitoring of the ECG during ablation for a change in QRS morphology should be considered to identify patients who will require further ablation. We have summarized in Table 1 important ECG characteristics indicative VA of specific origins, based on the findings of this study and previous studies in the literature 3,8–15 …”
Section: Location Of Va Qrs Morphology Timingmentioning
confidence: 99%
“…Therefore, through analyzing the features of ECG, an accurate prediction of the OT-VA origins before the procedure can optimize the ablation result, reduce ablation duration, and avoid eventual operative complications. In fact, numerous studies [3][4][5][6][7][8][9][10][11] have already revealed a strong relationship between the characteristics of ECG and the sites (RVOT or LVOT) where OT-VA stems from.…”
Section: Background and Summarymentioning
confidence: 99%
“…Label selection. The available sites classification studies listed in 3,[5][6][7][8][9][10][11] were designed to distinguish LVOT and RVOT per patient. However, the sub locations under RVOT or LVOT are also important from a clinical prospective.…”
Section: Technical Validationmentioning
confidence: 99%
“…We have summarized in Table 1 important ECG characteristics indicative VA of specific origins, based on the findings of this study and previous studies in the literature. 3,[8][9][10][11][12][13][14][15] 14. Doppalapudi H, Yamada T, McElderry HT, Plumb VJ, Epstein AE, Kay GN.…”
Section: July 7 2020mentioning
confidence: 99%